Correlation Between Body Mass Index With The Incidence Of Preeclampsia - Tjipto, Claudia A.; Warsanto, JA; Pramono, Adi (JOURNAL OF WIDYA MEDIKA JUNIOR, 2019)
Introduction: Indonesia is on its way to achieve the Millennium Development Goals (MDG’s) of reducing the maternal mortality ratio by three-quarters between 1990 and 2015. Preeclampsia was the second cause of maternal mortality in Indonesia that was 7-10% from all maternal mortality that happened. Preeclampsia is a disease that occurs during pregnancy, which usually appear after 20 weeks and is characterized by an increase in blood pressure during pregnancy (systolic/diastolic ≥140/90 mmHg) with proteinuria and edema. Research shows an association between high Body Mass Index with an increase in the occurrence of preeclampsia. Aim: This research purpose is to determine the correlation between Body Mass Index with incidence of preeclampsia. Methods: This research used an observational analytic cross-sectional design. The sample used was 46 data from mother with preeclampsia and 46 from mother with normal pregnancy. The data used were secondary data from X hospital on January 2014 until December 2015, selected based on the inclusion and exclusion criteria. Data analysed using Spearman test. Result: Preeclampsia was significantly correlated to high body mass index (p=0,000, correlation coefficient is 0,632), where 58.7% of obese mothers, 28.26% of overweight mothers were diagnosed with preeclampsia, while only 8.7% of normal weight mothers, and 4.34% of underweight mothers had preeclampsia. Conclusion: The results showed that there was a significant correlation between Body Mass Index and preeclampsia , suggesting that mothers with high body mass index were at a higher risk of preeclampsia